Nurses lived experiences of conscience reaction: a qualitative phenomenological study (Bangladesh Journal of Bioethics, 2012)
Background and objectives: Conscience is a cornerstone of ethics, affecting both our private and professional lives. Everyday health care practice raises questions about conscience and how to understand its role. Conscience has also been described as inducing self-growth and protecting personal integrity. Nurses views on their reactions to behaviors consistent or contrary to conscience could therefore help us to understand the meaning of the reactions of conscience. This study aimed to illuminate meanings of nurses lived experience of conscience reaction in their daily practices.Material and methods: Interviews with nine nurses were interpreted using a phenomenological hermeneutic (Colaizzi, 1978) method. Data was collected in 2010 among nurses working in various hospitals in Kermanshah. The nurses were selected for participation purposively.Results: The nurses lived experience of conscience reaction was formulated in three themes and ten sub-themes. The first theme is being peace, which includes three sub-themes: Being calm, being pleased, and being satisfying. The second theme is trouble conscience which includes four subthemes: guilt, thinking engagement, discomfort, and fretfulness. The third theme is responding which includes three sub-themes: expressing, compensation, and lack of repeat.Conclusions: The nurses lived experience of conscience reaction showed that nurses considered conscience reaction to be an important factor in the exercise of their profession, as revealed by the descriptive categories: being peace when they act consistent with conscience; trouble conscience when they act contrary on conscience; and responding after doing an anti conscience practice. They perceived that conscience played a role in nursing actions involving patients and next of kin, and guided them in their efforts to provide high quality care.  DOI: http://dx.doi.org/10.3329/bioethics.v2i3.10257Bangladesh Journal of Bioethics 2011;2(3):3-9